The effects of Nembutal on the intracerebellar EEG activity revealed by spectral and fractal analysis - Stojadinović, Gordana; Martać, Ljiljana; Podgorac, Jelena; Spasić, Slađana Z.; Petković, Branka; Sekulić, Slobodan; Kesić, Srđan (Archives of Biological Sciences, 2020)
Paper description: Studies of the effects of anesthetics on functional brain networks are essential to understand changes in brain bioelectrical activity in health and disease. Using spectral and fractal analysis, we recorded the electroencephalographic (EEG) activity at different layers of the cerebellum during nembutal anesthesia. Nembutal induced an increase in delta (0.1-4.0 Hz) and a decrease in theta (4.1-8.0 Hz) EEG frequency ranges, and an increase in the value of Higuchi’s fractal dimension in the cerebellar layers. This study indicates that spectral and fractal analysis can be used complementarily for measuring anesthesia-induced intra-cerebellar EEG dynamics. Abstract: A detailed analysis of the anesthetic-induced modulation of intracerebellar electrical activity is an important step to understand the functional brain responses to anesthesia. We examined the electrical activity recorded from different cortical layers: molecular layer (ML), Purkinje cell layer (PCL), granular layer (GL) and the white matter (WM) in the vermian part of rat cerebellar lobule V during Nembutal anesthesia using spectral and fractal analysis. Spectral analysis revealed a difference in the mean relative power of delta (0.1-4.0 Hz) and theta (4.1-8.0 Hz) frequencies through the cerebellar layers. Compared to the ML, delta activity increased significantly in the GL, while theta activity decreased in the GL and the WM. Fractal analysis revealed that the mean value of Higuchi’s fractal dimension (HFD) increased, starting from the ML to the WM. Theta activity exhibited a negative correlation with the HFD value in the ML. In contrast, the gamma activity showed a positive correlation with the HFD value in the ML and the GL. The combined use of spectral and fractal analyses revealed that Nembutal displays different effects on rat cerebellar electrical activity, which largely depends on the neurochemical and electrophysiological organization of the cerebellar layers. https://doi.org/10.2298/ABS200524036S Received: May 24, 2020; Revised: July 3, 2020; Accepted: August 6, 2020; Published online: August 27, 2020 How to cite this article: Stojadinović G, Martać L, Podgorac J, Spasić SZ, Petković B, Sekulić S, Kesić S. The effects of Nembutal on the intracerebellar EEG activity revealed by spectral and fractal analysis. Arch Biol Sci. 2020;72(3):425-32.